Composition of airport pavements and their particularities (Research, Society and Development, 2020)
This work aimed to expose, analyze and evaluate the composition of airport pavements with their design and construction peculiarities. Through indirect documentation, a bibliographic search was carried out identifying the differences between airport and road pavements in relation to their structure and engineering. First, the structure of a pavement was presented in general, types of pavements and coverings. Subsequently, Brazilian airport pavements were analyzed, observing their dimensioning methodology, which is oriented according to international standards. Then, the relationships between airport and road pavements were established and the similarities and differences between the two modalities were identified. Finally, the efficiency of an airport pavement structure and its particularities was presented.